RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

High-resolution skin-like microlithographic displays for visual-tactile system - Baoying Sun; Xiaoli Zhao; Chuang Xue; Mingxin Zhang; Pengbo Xi; Guoqiang Ren; Hao Liu; Junru Zhang; Yanping Ni; Yanhong Tong; Liangwen Feng; Qingxin Tang; et al. (Chemical Engineering Journal, 2026)

Pou4f3 Deficiency Obstructs the Subtype Differentiation of Vestibular Hair Cells - Qin Zhou; Yikang Huang; Wenli Ni; Mingchuan Feng; Lingjie Wu; Chuijin Lai; Yanping Zhang; Wenyan Li; Yan Chen (Neuroscience Bulletin, 2026)

Targeting Phospholipid Metabolism as an Effective Hearing Protection Strategy - Huanyu Mao; Wenli Ni; Lupeng Ma; Xiang Li; Yanping Zhang; Yuzheng Zhao; Wenyan Li; Huawei Li; Yan Chen (Neuroscience Bulletin, 2026)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Aquaporin ZmPIP2;4 promotes tolerance to drought during arbuscular mycorrhizal fungi symbiosis - Ying Ni; Hui Bao; Ruifan Zou; Yanping Wang; Kailing Xie; Beijiu Cheng; Xiaoyu Li (Plant and Soil, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

A SCYL2 gene from Oryza sativa is involved in phytosterol accumulation and regulates plant growth and salt stress - Minyan Xu; Ying Ni; Yaling Tu; Yanping Wang; Zhi Zhang; Yuhuan Jiao; Xin Zhang (Plant Science, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

A Novel N Self-Doped Porous Biochar Synthesized by KHCO3-Activated Chicken Feather for the Remediation of Tetracycline-Contaminated Water and Soil - Yu Deng; Jingfan Chen; Zhidan Xiao; Jiaying Liu; Jie Zhang; Bingqi Zhu; Xiaotong You; Fuquan Ni; Tianqi Ao; Yanping Tan (Water, Air, & Soil Pollution, 2024)

Highly Sensitive Detection of PIK3CA Mutations by Looping-Out Probes-Based Melting Curve Analysis - Boheng Xu; Yanping Lan; Danjiao Luo; Yangsi Zheng; Runfang Ni; Guoqiang Su; Qiuying Huang; Qingge Li (Biochemical Genetics, 2024)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Histone modification landscape and the key significance of H3K27me3 in myocardial ischaemia/reperfusion injury - Le Ni; Bowen Lin; Yanping Zhang; Lingjie Hu; Jianghua Lin; Fengmei Fu; Meiting Shen; Can Li; Lei Chen; Jian Yang; Dan Shi; Yi-Han Chen (Science China Life Sciences, 2023)

The regulatory gene wblA is a target of the orphan response regulator OrrA in Streptomyces coelicolor - Yanping Zhu; Xinyuan Wang; Jing Zhang; Xue Ni; Xia Zhang; Meifeng Tao; Xiuhua Pang (Environmental Microbiology, 2022)
Summary Our previous study using transposon mutagenesis indicated that disruption of the putative response regulator gene orrA impacted antibiotic production in Streptomyces coelicolor . In this study, the role of OrrA was further characterized by comparing the phenotypes and transcriptomic profiles of the wild‐type S . coelicolor strain M145 and Δ orrA , a strain with an inactivated orrA gene. Chromatin immunoprecipitation using a strain expressing OrrA fused with FLAG showed that OrrA binds the promoter of wblA , whose expression was downregulated in Δ orrA . The interaction of OrrA with the wblA promoter was further validated by a pull‐down assay. Similar to Δ orrA , the deletion mutant of wblA (Δ wblA ) was defective in development, and developmental genes were expressed at similar levels in Δ orrA and Δ wblA . Although both OrrA and WblA downregulated actinorhodin and undecylprodigiosin, their roles in regulation of the calcium‐dependent antibiotic and yellow‐pigmented type I polyketide differed. sco1375 , a gene of unknown function, was identified as another OrrA target, and overexpression of either s co1375 or wblA in Δ orrA partially restored the wild‐type phenotype, indicating that these genes mediate some of the effects of OrrA. This study revealed targets of OrrA and provided more insights into the role of the orphan response regulator OrrA in Streptomyces .

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Detection of virus in CSF from the cases with meningoencephalitis by next-generation sequencing - Hongzhi Guan; Ao Shen; Xia Lv; Xunzhe Yang; Haitao Ren; Yanhuan Zhao; Yinxin Zhang; Yanping Gong; Peixiang Ni; Honglong Wu; Yicheng Zhu; Liying Cui (Journal of NeuroVirology, 2016)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)